DESAIN GENERATOR OZONE DENGAN TEKNOLOGI PLASMA DBD (Die-lectric Barrier Discharge) - Aryadi, Ricky; Supari, Supari; Harmini, Harmini (Universitas Semarang, 2019)
Industrial sterilization is a very important problem. Ozone is a powerful oxidizer that can function for sterilization and is environmentally friendly. Plasma DBD (Dielectric Barrier Discharge) is one of the effective technologies to obtain ozone. The ozone generator currently uses a lot of manual control operations. Manual control uses a mechanical system in the form of a potentiometer to calibrate the frequency and output of the ozone generator output, so that digitization and automation are needed to operate to replace human labor. The design of the digital ozone control generator is done using an AVR microcontroller. Programming used in this research is basic language (BASCOM), then uses a DAC (Digital to Analog Converter) system which is the output of a Microcontroller with a Weighted Binnary Resistor. The output of the microcontroller is frequency and 8 bit digital with a decimal parameter of 200. The result of automation is that the timer works for 2 hours. The greater frequency the ozone produced. At a frequency of 1500Hz the power produced is 308.58 watts with an ozone concentration of 59 ppm. Efficiency using a switching system> 90%. Keywords: Plasma, AVR Microcontroller, Ozone.